Comparison of quality of life and sleep of adolescents with and without type 1 diabetes mellitus - Cordeiro, Gabriel Ribeiro (2020)
Type 1 Diabetes Mellitus (DM1) is an autoimmune disease that affects thousands of people today, with a higher concentration of cases in adolescence. Treatment involves lifestyle changes that can have a negative influence on quality of sleep (QS) and quality of life (QL). The purpose of the study was to compare QS and QL among adolescents with and without DM1. Seventy-four adolescents participated in the study divided by groups and sex: GDM1-F (n=19), GDM1-M (n=18), GC-F (n=21) and GC-M (n=16). The instruments used were the Pittsburgh Sleep Quality Index and WHOQOL-bref. Age-adjusted Covariance Analysis with Bonferroni Post Hoc was used to compare the groups. The results show that the participants of GDM1-F and GDM1-M, with DM1, had higher scores in all evaluations, with significant difference with CG-F in the variables: global QS, Physical, Psychological and Social Relationships and total QL. Therefore, it was possible to observe that adolescents with DM1 had better QS and QL evaluations than girls without DM1, regardless of age.